2009
DOI: 10.1161/circresaha.109.194613
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Sphingomyelin Synthase 2 Deficiency Decreases Atherosclerosis in Mice

Abstract: Rationale: Sphingomyelin synthase (SMS)2 contributes to de novo sphingomyelin (SM) biosynthesis and plasma membrane SM levels. SMS2 deficiency in macrophages diminishes nuclear factor B and mitogen-activated protein kinase activation induced by inflammatory stimuli. Objective: The effects of SMS2 deficiency on the development of atherosclerosis are investigated. Methods and Results: We measured cholesterol efflux from macrophages of wild-type (WT) and SMS2 knockout (KO) mice. We transplanted SMS2 KO mouse bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 43 publications
4
106
1
Order By: Relevance
“…Mammals contain two SMS isoforms, namely SMS1, primarily responsible for de novo SM synthesis in the lumen of the trans Golgi, and SMS2, presumably serving a role in regenerating SM from ceramides liberated by SMases on the cell surface (12)(13)(14)(15). Studies in mice revealed a role of SMS1 and SMS2 in inflammation, atherosclerosis, and dia betes (15)(16)(17), suggesting that these enzymes represent rel evant pharmacological targets. Besides bulk amounts of SM, mammals also produce small quantities of ceramide phos phoethanolamine (CPE), a widespread but poorly studied SM analog.…”
Section: Synthesis Of Clickable Ceramide Analogmentioning
confidence: 99%
“…Mammals contain two SMS isoforms, namely SMS1, primarily responsible for de novo SM synthesis in the lumen of the trans Golgi, and SMS2, presumably serving a role in regenerating SM from ceramides liberated by SMases on the cell surface (12)(13)(14)(15). Studies in mice revealed a role of SMS1 and SMS2 in inflammation, atherosclerosis, and dia betes (15)(16)(17), suggesting that these enzymes represent rel evant pharmacological targets. Besides bulk amounts of SM, mammals also produce small quantities of ceramide phos phoethanolamine (CPE), a widespread but poorly studied SM analog.…”
Section: Synthesis Of Clickable Ceramide Analogmentioning
confidence: 99%
“…5F), whereas no change was observed in the expression of the other genes. We previously reported that the COS treatment may promote the expression of LXR in the liver 14) . In the present study, we additionally found that the LXR expression was significantly enhanced with the treatment of COS (Fig.…”
Section: Effects Of the Cos Treatment On Cultured Hepg2 Cells And Rawmentioning
confidence: 99%
“…The aortas were dissected and the arches were exposed for photographing 14) . A quantitative analysis of an aortic lesion en face assay was performed as previously described 14,15) .…”
Section: Atherosclerosis Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis was determined as previously described ( 19 ). Briefl y, Pltp KO/ Apoe KO and Apoe KO mice were fed the high-fat diet for 7 weeks.…”
Section: Quantitative Analysis Of Atherosclerosismentioning
confidence: 99%